Using Logistic Regression to Estimate the Influence of Adolescent Sexual Behavior Factors on Students of Senior High School 1 Sangatta, East Kutai-East Kalimantan - Darnah Darnah; Memi Norhayati (UPT Penerbitan Universitas Jember, 2016)
Adolescence is a transitional stage of physical and psychological development that generally occurs during the period from puberty to legal adulthood. Puberty is the time in which a child's sexual and physical characteristics mature. Adolescents have been found at high risk for many negative health consequences related to sexual risk-taking behavior, including infection with human immunodeficiency virus, other sexually transmitted disease, and unintended pregnancy. This research aims to determine the relationship between the reproductive health knowledge and using gadget with adolescent sexual behavior using chi- square test. Additionally, binary logistic regression was used to modeling it. Subjects in this research are students of Senior High School 1 Sangatta, East Kutai-East Kalimantan. The research shows that reproductive health knowledge has a relationship with adolescent sexual behavior. The students have reproductive health knowledge are good to have adolescent sexual behavior unrisk 2.6 more than students have reproductive health knowledge are bad.